2021
DOI: 10.48017/diversitas_journal-v6i3-1273
|View full text |Cite
|
Sign up to set email alerts
|

Impacto do pré dipping, padrão racial e ordem dos jatos de leite sobre a atividade microbiológica e físico-química do leite cru bovino

Abstract: Impacto do pré dipping, padrão racial e ordem dos jatos de leite sobre a atividade microbiológica e físico-química do leite cru bovino Impact of pre-dipping, racial pattern and order of milk jets on the microbiological and physical-chemical activity of raw bovine milk Neilson Silva Santos (1) ; Cléber Fontes de Medeiros (2) ; José Crisólogo de Sales Silva (3) ; Cleyton de Almeida Araújo (4) ; Thayse Cristina de Freitas Sarmento (5) ; Cintia Nunes Fontes (6)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Considering that the values presented in the variables are discrete, an approach such as ordinal categorical, has positive effects on the adoption of pre-dipping (Santos et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the values presented in the variables are discrete, an approach such as ordinal categorical, has positive effects on the adoption of pre-dipping (Santos et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Prevention takes place through pre-dipping and post-dipping hygienic-sanitary prophylactic treatment, among others. Santos et al (2021) found that the adoption of pre-dipping technique reduces the number of bacteria.…”
Section: Introductionmentioning
confidence: 99%